ANALISIS YURIDIS TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA SECARA MELAWAN HUKUM (Studi Kasus 84/Pid.Sus/2023/PN Mdn - Silaban, Dandy; Feby Florenza Br Sembiring; Annisa Puspitasari; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (Jurnal Paris Langkis, 2023)
Crimes whose perpetrators are subject to universal principles, which can be described as acts or crimes that are categorized as crimes against the enemy of humanity, include: narcotics crimes, terrorism, airplane hijacking, genocide, etc. This research contains narcotics crimes with Decision Number 84/Pid.Sus/2023/PN Mdn. This research uses secondary data or library materials only. This research is included in the library research category. The problem that the author wants to study is the stages of implementation of the decision process in case number 84/Pid.Sus/2023/PN Mdn. Declare that the defendant Eriko Alias Eko has been legally and convincingly proven guilty of committing the crime of "unlawfully or unlawfully acting as an intermediary in the sale and purchase of class I narcotics"; Sentencing the defendant to imprisonment for 5 (five) years and a fine of IDR 1,000,000,000.00 (one billion rupiah); Stipulating that if the fine is not paid it will be replaced by a prison sentence of 4 (four) month; Determines that the period of arrest and detention that has been served by the Defendant shall be reduced in full by the sentence imposed.